A política de gestão de pessoas: um olhar sobre a movimentação docente no contexto da interiorização e expansão da Rede de Educação Profissional e Tecnológica - Martins, Patrícia Deisymar Silva (2022)
In view of the expansion and internalization of the Federal Institutes (IFs), there was the entry of new professors and technical-administrative staff in newly created campuses, generating a great movement of these servers in the Federal Network of Professional and Technological Education. In this context, as the People Movement Coordinator, I observed a significant number of demands for removal within the scope of the Instituto Federal do Sertão Pernambucano (IFSertãoPE), with the consequent attendance and significant turnover of teachers in the Institution, this phenomenon aroused my interest in carrying out this research, which aims to analyze the policy of movement of people of the IF Sertão, namely the internal removal, from the perspective of the professors attended or not in their demands. Initially, an exploratory study was carried out in the Northeast Institutes, with a look at the removal of professors in the Region, as a parameter for understanding the phenomenon experienced in the IF locus of the research. The research, of a qualitative nature, was developed through document analysis, bibliographical study and pertinent legislation, with the application of semi-structured questionnaires directed to the teachers of the Instituto Federal do Sertão Pernambucano who requested removal in the period from 2017 to 2020. The results obtained point out that teaching staff are motivated to request removal mainly due to family issues and the lack of structure on their campus. It was evident that the IF Sertão needs to encourage the server to remain on the home campus, in order to maintain a staff engaged and motivated to work in the Institution. The challenge lies with the development of a management policy that employees feel motivated to contribute effectively to the institution, which seeks to balance the needs of the campus and the demands of professors.